THE REQUEST STRATEGY OF SUMATRAN INFORMANTS IN PERFORMING SPEECH ACTS REQUEST - Yulita, Delti; Siahaan, Desta Gloria (Jurnal Edulanguage: Jurnal Pendidikan Bahasa, 2021)
This present study was proposed to investigate the notion of request speech acts among native Sumatran. The informants took a Discourse Completion Test (DCT) consists of eight scenarios and respond it based on the situation given. The responses were analyzed by directness categories in scale designed by Blum-Kulka et al (1984) named Cross-Cultural Study of Speech Act Realization Patterns (CCSARP). The result shows that Sumatran informants mostly use conventionally indirect request as a strategy in formulating request speech acts. The outcomes revealed that a high number of politeness marker is employed along with grounded as parts of external and internal modification in request performing.